2017
DOI: 10.2139/ssrn.3120363
|View full text |Cite
|
Sign up to set email alerts
|

One Size Does Not Fit All: A Field Experiment on the Drivers of Tax Compliance and Delivery Methods in Rwanda

Abstract: This is an Open Access paper distributed under the terms of the Creative Commons Attribution Non Commercial 4.0 International license, which permits downloading and sharing provided the original authors and source are credited -but the work is not used for commercial purposes. http://creativecommons.org/licenses/by-nc/4.0/legalcode SummaryAlthough field experiments in tax compliance represent a growing area of research, the literature has so far focussed exclusively on high and middle-income countries. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Further evidence on fiscal exchange comes from a recent field experiment from Rwanda (Mascagni et al ., ). In this context, as in low‐ and middle‐income countries more generally, non‐compliance with the treatment is a greater concern because taxpayer registries are often incomplete or not kept up to date .…”
Section: Review Of Tax Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Further evidence on fiscal exchange comes from a recent field experiment from Rwanda (Mascagni et al ., ). In this context, as in low‐ and middle‐income countries more generally, non‐compliance with the treatment is a greater concern because taxpayer registries are often incomplete or not kept up to date .…”
Section: Review Of Tax Experimentsmentioning
confidence: 97%
“…This was done in a recent study, where the same messages were delivered through three delivery methods (Mascagni et al, ). This study, reviewed in more detail in section , shows that non traditional delivery methods like emails and SMS can be highly effective compared to letters in low‐income countries.…”
Section: Review Of Tax Experimentsmentioning
confidence: 99%
“…Other non-deterrence nudges: The second sub-category of non-deterrence nudges mainly contains manipulations that are utilized "to correct" the taxpayer non-compliance that stems from such behavioral fallacies as limited attention, procrastination and cognitive overload among others. For instance, simple reminders are sent to taxpayers to overcome the problem of limited attention (Hernandez et al 2017, Mascagni et al 2017. The problem of cognitive overload is usually bypassed through the simplification of the communication language, the introduction of visual stimuli or provision of information how to file the income (De Neve et al 2019, Eerola et al 2019.…”
Section: Tax Compliance Measures and Types Of Nudgesmentioning
confidence: 99%
“…As noted above, an experiment in Rwanda found that letters to taxpayers stressing the connections between taxes and services were generally at least as effective as enforcement threats in increasing compliance. 141 Still, communication-based interventions may have a limited ceiling, or diminishing returns. Telling taxpayers about the link between tax payments and public services is unlikely to be a substitute for actual improvements in public services in a context where citizens are generally dissatisfied.…”
Section: Reciprocitymentioning
confidence: 99%